Control interno y su incidencia en las contrataciones públicas de la Municipalidad Provincial de Ucayali, Contamana, 2022 - Da'Silva Lopez, Maria Jesus (2023)
The objective of this project was to determine the internal control and its impact on public procurement of the Provincial Municipality of Ucayali 2022; Applied study, explanatory-casual level and non-experimental design, likewise, 30 officials were taken as population, who were surveyed through a questionnaire. Among its results, it was evident that internal control in this institution is regular (30%), because control activities are almost never carried out independently; As well, management sometimes communicates with external stakeholders on key issues. Regarding public procurement, it is evident that 27% qualify it as regular, since the PAC is sometimes published in the SEACE and in the institutional portal of the Municipality, but there are almost never exceptional parameters for the determination of contracting services and specialized consulting. Finally, it was concluded that internal control has a significant impact on public procurement, with a considerable correlation index of 0.740 and a significance level of 0.000; Likewise, for the dimensions Control Environment (R=0.628, P=0.000), Information and Communication (0.512; p=0.004), Supervision and Monitoring (0.427; P=0.038) they obtained a medium-level correlation, for risk assessment a considerable correlation (0.725; p= 0.000); Finally, the dimension Control activities weak correlation (0.402; p = 0.027).